IMPROVING TAX ADMINISTRATION THROUGH ELECTRONIC TAX SYSTEMS AND THEIR ECONOMIC EFFICIENCY - Turayev Alijon Akmalovich; Ilamonov Mexroj Akbar o‘g‘li (TADQIQOTLAR, 2026)
Abstract. The digital transformation of tax administration has become a key reform strategy for improving revenue collection, reducing compliance costs, and combating tax evasion. Based on data from the OECD, IMF, and case studies from Estonia, Rwanda, Brazil, and Uzbekistan, this study shows that electronic filing, e- payment, and integrated tax systems help reduce the tax gap, lower administrative costs, and enhance taxpayer compliance. The article concludes with policy recommendations to further improve the effectiveness of electronic tax systems and maximize their economic benefits.